Building a weakly outgassing comet from a generalized Ohm’s law - Deca,J; Henri,P; Divin,A; Eriksson,A; Galand,M; Beth,A; Ostaszewski,K; Horányi,M (Physical Review Letters, 2019)
When a weakly outgassing comet is sufficiently close to the Sun, the formation of an ionized coma results in solar wind mass loading and magnetic field draping around its nucleus. Using a 3D fully kinetic approach, we distill the components of a generalized Ohm’s law and the effective electron equation of state directly from the self-consistently simulated electron dynamics and identify the driving physics in the various regions of the cometary plasma environment. Using the example of space plasmas, in particular multispecies cometary plasmas, we show how the description for the complex kinetic electron dynamics can be simplified through a simple effective closure, and identify where an isotropic single-electron fluid Ohm’s law approximation can be used, and where it fails.